Tuning electronic and optical properties of arsenene/C3N van der Waals heterostructure by vertical strain and external electric field. (11th January 2018) - Zeng, Hui; Zhao, Jun; Cheng, Ai-Qiang; Zhang, Lei; He, Zi; Chen, Ru-Shan
Abstract: Searching for new van der Waals (vdW) heterostructure with novel electronic and optical properties is of great interest and importance for the next generation of devices. By using first-principles calculations, we show that the electronic and optical properties of the arsenene/C3 N vdW heterostructure can be effectively modulated by applying vertical strain and external electric field. Our results suggest that this heterostructure has an intrinsic type-II band alignment with an indirect bandgap of 0.16 eV, facilitating the separation of photogenerated electron–hole pairs. The bandgap in the heterostructure can be tuned from 0–0.35 eV via the strain, experiencing an indirect-to-direct bandgap transition. Moreover, the bandgap of the heterostructure varies linearly with respect to a moderate external electric field, and the semiconductor-to-metal transition can be realized in the presence of a strong electric field. The calculated band alignment and the optical absorption reveal that the arsenene/C3 N heterostructure could present excellent light-harvesting performance. Our designed vdW heterostructure is expected to have great potential applications in nanoelectronic devices and photovoltaics.